An appraisal of ICAR-IISR released varieties in spices - M S, Shivakumar; H J, Akshitha; Aarthi S; Nissar, V A Muhammad; T E, Sheeja (Indian Horticulture, 2025)
This study evaluates the performance of ICAR-IISR released spice varieties, focusing on key crops such as black pepper, cardamom, ginger, turmeric, nutmeg, and cinnamon. Employing a range of conventional and modern breeding strategies, including clonal and germplasm selection, hybridization, mutation breeding, and biotechnological tools, the research examines yield, quality attributes (e.g., essential oil, oleoresin, curcumin content), and resistance to biotic and abiotic stresses. Data from multi-location trials reveal that improved varieties such as Sreekara and IISR Girimunda (black pepper), Appangala 2 and IISR Vijetha (cardamom), IISR Vajra (ginger), IISR Pragati and Prathibha (turmeric), Viswashree and Keralashree (nutmeg), and Navashree and Nithyashree (cinnamon) consistently outperform traditional cultivars in productivity, metabolite content, and resilience.